Os reflexos da educação formal na atuação da enfermeira na atenção básica - COSTA, Gláucia Jacklinne Almeida da (2019)
The study aims to unveil the reflections of formal education in the practice of nurse in the basic attention. The methodology focuses on qualitative research, case study type. The scenario of research was a basic health Unit (BHU), located in a neighborhood of the city of Parramatta. The subjects of this study were crowded in the unit, total four (04). The data were collected through semistructured interview with Protocol containing four (04) questions. The data were analysed and described in thematic categories and sub-categories. This process emerged two (02) categories: i. "formal education: foundations for the development of professional practice" and II. "Professional practice: clashes in the everyday life of the basic attention" and four (04) subcategories: "the process of teaching in academic training", "contribution of academic training to professional practice", "difficulties for professional performance" and "ways to improve professional performance." The results made it possible to note that even with a change in the formation of the professional Nurse, yet one senses the presence of a traditional education in performance of this professional in the basic attention. It is therefore concluded that with the increasing changes in the globalized world and accelerated scientific and technological modernization process, the Formal Education serves as an important tool for the formation of the professional Nurse, contributing positively to performance of this in society. And yet, have been required a professional generalist, critical and reflective, such teaching model come suffering even today, interference of teaching process traditionalist.